YWCA 1926 cornerstone box - Unknown:::Creator::::::::::::
Photograph is of Mary Root, Inez Jackson, Lois Cullison, and Mrs. John Goldsborogh standing at a table with items from the 1926 cornerstone box. The box is on the table by Mrs. Goldsborogh and she is holding a sheet of paper that she may be reading from. A group of women are in seats in the background.